This land: politics, authority and morality after land reform in Zimbabwe - Sinclair-Bright, Leila Tafara (The University of Edinburgh, 2016)
This thesis examines people’s attempts to (re)construct belonging and authority after rapid socio-political and economic change. It is a study of the lives of those living alongside each other in a new resettlement area in Zimbabwe a decade after ‘fast track’ land reform. Drawing on ethnographic research conducted on a series of farms in the Mazowe area (March 2012-May 2013), I show that in the uncertain socio-political context of this new resettlement area, belonging was a dynamic social process involving complex moral bonds, and relationships of dependence and obligation. ‘Fast track’ land reform can be understood as a process of state-making in which the Zimbabwean state reconfigured its relationship with its citizens via the redistribution of land. After ‘fast track’, farms were transformed from socially and politically bounded entities under the paternalistic rule of white farmers, to areas in which land beneficiaries and farm workers lived alongside one another under the rule of the ZANU PF state. Land was allocated according to ZANU PF loyalty. Farmworkers due to their associations with white farmers and oppositional politics, were rarely allocated land. Thus farms in Mazowe consisted of landless farm workers who had lived and worked in the area for generations, and landed beneficiaries who came from a variety of places. In addition, ‘fast track’ was framed in terms of redistribution rather than restitution but many chiefs saw it as an opportunity to ‘return’ to their ancestral lands. However, their claims to authority in the areas remained uncertain. I examine how people dealt with the various tensions thrown up by ‘fast track’. By leaving these tensions unresolved, a contingent stability was generated on farms, even as this was fragile. My work contributes to better understanding the socio-political effects of land reform. Research on Zimbabwean land reform has tended to rely on official framings of people’s relationships to each other and the land, and has largely failed to capture the complexity and negotiated nature of these in everyday life. Anthropological work on belonging has mostly focused on explicit claims. I show how history and the micro-politics of everyday relationships profoundly shaped local forms of belonging which crosscut state delimitations of who belonged, and what land reform meant to those living in this area.
Keywords: Zimbabwe; land reform; politics of belonging; Mazowe; ethnography